FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Zainal Alim Adiwijaya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study is intended to identify and analyze the influence of auditor ethics, skepticism, professionalism and competence on audit quality at the inspectorate of Grobogan Regency, Central Java. The sample to be analyzed is the inspectorate unit of Grobogan Regency, Central Java who understands auditing procedures. The sampling method that will be used is the census method with a total sample of 54 respondents. Data analysis techniques used include instrument testing, classical assumption test, hypothesis testing and coefficient of determination. The results of the research analysis show that auditor ethics, skepticism, professionalism and competence have a positive and significant effect on the results of audit quality at the Grobogan inspectorate agency.